2019
DOI: 10.24853/elif.2.1.43-52
|View full text |Cite
|
Sign up to set email alerts
|

Theme Based Instruction Model in Teaching Extensive Reading

Abstract: The purpose of this study is to investigate in detail the implementation of theme based instruction model  in teaching extensive reading. This study is classroom action research conducted at the fourth semester students’ English Educational Sciences, Educational Sciences Faculty, Universitas Muhammadiyah Jakarta with participant number are 40 students. Data obtained from the result of the test in each cycle. The findings showed that the learning process using theme based instruction model  in teaching extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition, to enhance students' reading competence, it is suggested that a theme-based English learning model be implemented, incorporating the ADDIE model for instructional design and integrating the Content and Language Integrated Learning (CLIL) method (Subaedah, Bundu, & Yahya, 2023). Similarly, another study aims to thoroughly examine the application of the theme-based instruction model in the context of lengthy reading instruction (Mutiarani & Rahman, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, to enhance students' reading competence, it is suggested that a theme-based English learning model be implemented, incorporating the ADDIE model for instructional design and integrating the Content and Language Integrated Learning (CLIL) method (Subaedah, Bundu, & Yahya, 2023). Similarly, another study aims to thoroughly examine the application of the theme-based instruction model in the context of lengthy reading instruction (Mutiarani & Rahman, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Concept of TBLT As one of the most often used techniques to L2 education, TBLT, one model of communicative language teaching (CLT), is increasingly essential (Crookes & Ziegler, 2021). It is stated that the TBLT is a cutting-edge strategy used in high schools, language institutes, and lower to advanced levels (Mutiarani & Rahman, 2019). The national curriculum has stipulated that theme-based language teaching be used as a novel instructional strategy that immerses students in "Highly Contextualized" language and subject-specific contexts (Tussa'diah & Nurfadillah, 2018).…”
Section: Task-based Language Teaching (Tblt)mentioning
confidence: 99%
“…From that, all the learners are learning English with different style according their levels of understanding. The government as the main holder of education in Indonesia still searching and adaptating the best learning method, strategy and approach to make the students fluent in mastering English and become like a native speaker (Mutiarani & Rahman 2019). Alderson (2000) mentions reading, through which readers can access worlds of ideas and feelings, as well as the knowledge of ages and visions of the future, is at once the most extensively researched and the most enigmatic of the so-called language skills.…”
Section: Introductionmentioning
confidence: 99%